The Influence of Leadership Style, Work Motivation, and Organisational Culture On Employee Retention At SPD Communication - Echa Ferina Br. Purba; Eli Delvi Yanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study examines the influence of leadership style, work motivation, and organisational culture on employee retention at SPD Communication. The high employee turnover rate has become a serious problem for many companies, including SPD Communication, which has an impact on productivity and operational costs. The purpose of this study is to analyse the extent to which these factors influence employees' desire to stay with the company. The research method used is a quantitative approach with a survey design. Data was collected through questionnaires distributed to 51 employees of SPD Communication. Data analysis was conducted using multiple linear regression methods to test the research hypothesis. The results showed that leadership style and work motivation have a positive and significant effect on employee retention, with t-count values of 7.768 and 2.934, respectively, which are greater than the t-table (2.01174) and significance less than 0.05. In contrast, organisational culture negatively affects employee retention. In contrast, organisational culture negatively affects employee retention with a t-count value of -2.459 and a significance of 0.018. ANOVA analysis shows that the three variables together can explain 63.6% of the variation in employee retention, with an F-value of 27.423 and significance <0.001.